Determination of Promising Peanut Lines in Northeastern Philippines - Bernabe, Jocelyn Aoalin (New Approaches in Engineering Research Vol. 11, 2021)
The present study aimed to adapt, evaluate, select and identify high yielding, disease-resistant and other desirable characters of peanut in northeastern Philippines particularly at Mariano Marcos State University (MMSU), Dingras, Ilocos Norte, conducted from July 2014 to May 2015. Peanut or ground nut (Arachis hypogea L.) is one of the food legumes with commercial importance in the Philippines grown by farmers (with small landholdings) in most parts of the country. However, one of the major constraints to peanut is the lack of supply of good stocks coupled with modern production technology. To alleviate this problem especially in those areas planted to this crop is the development of improved lines, their evaluation to different locations and their maintenance for sustained production. The different lines of peanut were arranged in a randomized complete block design (RCBD) replicated four times. Optimum cultural requirements from planting to harvesting were followed to permit expressions of the genetic potential of the different lines of the crop. During wet and dry season trials, results revealed significant differences in all treatments relative to pod and seed yield, seed size, shelling percentage and plant height except number of pods per plant, and days to flower and mature. The lines ICGV 00337, ICGV 95111, and ICGV 98371 out yielded the remaining seven peanut lines registering a pod yield of 1,860 to 1,020 kg/ha and had a yield advantage of 73% to 58.9%, respectively over the check variety Ilocos Red. Growing peanut in northeastern Philippines can approximately give an income ranging from Php87,120 to Php93,960 per hectare with a benefit/cost ratio of 2.02 to 2.19. The results of the study would provide awareness to marginal farmers, peanut growers and other stakeholders especially in the northeastern Philippines, on the available promising peanut lines that can be grown during either or both wet and dry season.